The Problems of Estonian R&D and Innovation Strategy and the Demand-Side Innovation Policies - Roolaht, Tõnu (Estonian Discussions on Economic Policy, 2012)
The second larger Estonian R&D and Innovation Strategy ‘Knowledge-based Estonia 2007-2013’ is aimed at continuing the advancement of research and development efforts towards an innovative knowledge-based society and economic system in Estonia. Fostering of knowledge-based high-tech industries is seen as paramount for retaining country’s competitive advantage. However, the mid-term evaluations indicate that several goals of the strategy might not be achievable by 2013. In fact, the policy measures have been much more successful in developing scientific research, as indicated by increased international publication, number of patents, and number of researchers and engineers. The advances in development of high-tech products and services through innovations are noticeable but less prominent. The purpose of this study is to suggest the role for demand-side innovation policies in helping to advance commercial development and innovation